Patterns of calcitonin gene-related peptide monoclonal antibody use in people with migraine: Results of the OVERCOME (US) study - Ashina, Sait; Kim, Gilwan; Muenzel, E Jolanda; Buse, Dawn C; Zagar, Anthony J; Zakharyan, Armen; Shapiro, Robert E; Nicholson, Robert A; Pearlman, Eric M; Lipton, Richard B (Cephalalgia, 2025)
BackgroundUnderstanding characteristics and reasons associated with using calcitonin gene-related peptide monoclonal antibodies (CGRP mAb) for migraine prevention may help clinicians individualize treatment plans and achieve better patient outcomes.MethodsWe analyzed 2019-2020 cohort data of OVERCOME (US), a population-based survey among adults with migraine. Eligible participants were categorized based on current CGRP mAb usage ("NEVER" and "EVER" users ["Continued", "Switched" and "Discontinued"]). Machine learning techniques followed by logistic regression were used to examine, among 60 sociodemographic, clinical, migraine-related- and migraine treatment utilization characteristics, those associated with CGRP mAb use status.ResultsOf 39,113 participants, 25.6% had ever used migraine preventive medication(s) and 5.0% used CGRP mAbs (of which 46.1% Continued, 14.7% Switched and 39.3% Discontinued). Top factors associated with higher odds of CGRP mAb EVER vs. NEVER use were currently using recommended acute medication (odds ratio (OR) = 2.43; 95% confidence interval (CI) = 2.09-2.82) and contraindications for triptan use (OR = 2.32; 95% CI = 2.06-2.60). Continuing use vs. switching or discontinuing was most associated with current use of botulinum toxin for migraine (OR = 2.21; 95% CI = 1.42-3.44 and OR = 4.53; 95% CI = 3.14-6.55, respectively).ConclusionsAt the time of survey, CGRP-targeted mAbs remain underutilized for migraine and multiple characteristics are associated with CGRP mAb use patterns.